Evaluation of User Satisfaction in the Satusehat Application - Sulistianingsih Sulistianingsih; Mieke Nurmalasari; Hosizah Hosizah; Witri Zuama Qomarania (Jurnal Ilmu Kesehatan Masyarakat, 2024)
Digital transformation in the health sector aims to provide quality, fast, easy, affordable, and measurable services to the community. User satisfaction is paramount when providing services. Key factors influencing user satisfaction include Information, System, and Service Quality. The objective of this study is to evaluate the impact of information quality, system quality, and service quality on user satisfaction with the SATUSEHAT. This research used a quantitative with a cross-sectional design technique. This research using a quota sampling method with 106 respondents. This research using multiple linear regression analysis with univariate and multivariate classical assumption tests. This research focuses on SATUSEHAT application users who actively use social media platforms like Instagram and Twitter. The evaluation aims to provide insights into the impact of information, system, and service quality of the SATUSEHAT application's user satisfaction with the SATUSEHAT application. The results explain that 56.6% of respondents were female, 43.3% were male. 54.7% of this study's respondents were undergraduates aged 19 - 34 years, 67.0% of respondents. Most of the respondents' jobs were employees, 34.9%. Service quality significantly influences SATUSEHAT application The results of the regression coefficient value for user satisfaction is 0.651, and quality of the information, with a regression coefficient of 0.113. The The study found that information, system, and service quality significantly influence user satisfaction with the SATUSEHAT application.